Western European Source and the Meaning of the Iconography Christ The Great Hierarch with The Crucifix and Emmanuel: On the Problem of the Triple Images of Christ - Maier, Polina V. (Actual Problems of Theory and History of Art, 2016)
Iconographical innovations of the icons made to the order of bishop Makarij are the objects of our scientific research. The attention has been concentrated on multiple-purpose Christological iconograph- ical types, where images based on symbolical realism are combined with meta-historical images of Christ. As a result, practical and theoretical development of such iconographies in the mid-sixteenth century took hold of some iconographical types with multiple images of Christ. One of them — Christ The Great Hierarch with The Crucifix and Emmanuel — was inspired by Franciscan composition Quinitas. Western European principle of creating a picture as a theological statement by using visual gradation and subordination was known in icon-painting of Novgorod and Pskov. The scheme of Quinitas received an essential reduction and correlated with existing traditional iconographical schemes. The combination of several images of Christ in one semantic field of icon underlines the identity of Christ before, in and after incarnation. Meta-historical Christ, before and after incarnation, was depicted according to prophetical visions. The examined iconographical type presents an example of originally Russian visual theology. The combinatorial approach correlates with the imperative to collect and to accumulate, the key activities of Makarij. The interaction of Western European and Russian artistic traditions occurred in the examined case as assimilation of Franciscans pattern.
Keywords: Old Russian icon painting; iconographical school of metropolitan Makarij; Western European borrowings; 16th century; Polish medieval art; art of the Franciscans